Shift work and the risk of cardiovascular disease. A systematic review and meta-analysis including dose-response relationship - Luciana Torquati; Gregore I Mielke; Wendy J Brown; Tracy Kolbe-Alexander (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The aim of this review was to assess the risk of cardiovascular disease (CVD) events associated with shift work and determine if there is a dose-response relationship in this association. METHOD: Electronic databases (PubMed, Scopus, and Web of Science) were searched for cohort or case-control control study designs in any population, reporting exposure to shift work as the main contributing factor to estimate CVD risk. For each study, adjusted relative risk (RR) ratios and 95% confidence intervals (CI) were extracted, and used to calculate the pooled RR using random-effect models. Meta-regression analysis was conducted to explore potential heterogeneity sources. Potential non-linear dose-response relationships were examined using fractional polynomial models. RESULTS: We included 21 studies with a total of 173 010 unique participants. The majority of the studies were ranked low-to-moderate risk of bias. The risk of any CVD event was 17% higher among shift workers than day workers. The risk of coronary heart disease (CHD) morbidity was 26% higher (1.26, 95% CI 1.10-1.43, I^2= 48.0%). Sub-group analysis showed an almost 20% higher risk of CVD and CHD mortality among shift workers than those who did not work shifts (1.22, 95% CI 1.09-1.37, I^2= 0% and 1.18, 95% CI 1.06-1.32 I^2=0%; respectively). After the first five years of shift work, there was a 7.1% increase in risk of CVD events for every additional five years of exposure (95% CI 1.05-1.10). Heterogeneity of the pooled effect size (ES) estimates was high (I^2=67%), and meta-regression analysis showed that sample size explained 7.7% of this. CONCLUSIONS: The association between shift work and CVD risk is non-linear and seems to appear only after the first five years of exposure. As shift work remains crucial for meeting production and service demands across many industries, policies and initiatives are needed to reduce shift workers' CVD risk.